Liquefaction of oil palm fruit waste and its application for the development of polyurethane foams - Kormin, Shaharuddin; M. Rus, Anika Zafiah (Science Publishing Corporation (SPC), 2018)
This research utilizes solvolysis liquefaction of oil palm fruit waste (PW) biomass for production of polyurethane (PU) foam. Three part of PW: oil palm mesocarp fibre (PM), oil palm shell (PS) and oil palm kernel (PK) was treated using liquefaction solvent with sulfuric acid. Effects of different liquefaction condition such as effect of raw material/liquefaction solvent ratio, reaction time, liquefaction temperature, catalyst amount and liquefaction solvent on liquefaction yield have been determined. Analytical methods used were SEM and DSC analysis. Result showed that more than 70% of the PW were converted into biopolyols within optimum reaction condition of 120 minutes at 150°C with raw material/liquefaction solvent ratio of 1/3 using PEG400. In liquefaction process, hemicellulose, cellulose and lignin are degraded which results in changes of acid and hydroxyl value. Biopolyols of PM/PEG400 ratios was yielded highest biopolyol which is used to continue the experiment. Foaming kinetic indicate a slight increase from initial mix time to gelling time. Moisture content and water absorption are strongly affected the mechanical properties of PU foam. There is no Tg observed in PMF in DSC analysis. Oil palm fruit waste showed great potential for PU foams fabrication.